Randomised controlled trial of inhaled corticosteroids (fluticasone propionate) in cystic fibrosis. Issue 2 (1st August 1997) - Balfour-Lynn, Ian M; Klein, Nigel J; Dinwiddie, Robert
Abstract : BACKGROUND: Controlling lung inflammation may be the key to improving morbidity and mortality in cystic fibrosis. OBJECTIVE: To assess the effects of inhaled corticosteroids on lung inflammation in cystic fibrosis. DESIGN: Double blind placebo controlled randomised sequence crossover trial. Fluticasone propionate (400 μg/day) was given as a dry powder inhaler for six weeks with a four week washout period before crossover. OUTCOME MEASURES: Sputum inflammatory markers (interleukin-8, tumour necrosis factor-α (TNF-α) and neutrophil elastase—both free and bound to α1 -antiprotease), sputum interleukin-10, lung function, and symptomatology. SUBJECTS: Twenty three children from a regional cystic fibrosis centre were enrolled into the study, with mean age 10.3 years (range 7 to 17 years) and mean baseline forced expiratory volume in one second (FEV1 ) of 64% (range 21% to 102%) predicted for sex and height. One patient was excluded for non-compliance to the study protocol. RESULTS: No significant benefit was shown for the use of fluticasone propionate in any of the outcomes. For sputum interleukin-8 there was an estimated true treatment median difference of 142 pg/ml (95% confidence interval (CI) 8 to 2866 pg/ml) in favour of placebo; while for maximal expiratory flow at 25% (MEF25% ) remaining forced vital capacity predicted for sex and height there was a 15 percentage points (pp) (95% CI 4 to 26 pp) mean treatment difference in favour of placebo. Sputum interleukin-10 was undetected in any samples and unaffected by fluticasone propionate. Neither atopic status, baseline FEV1, nor concomitant DNase therapy had any effect on response to treatment. CONCLUSIONS: Lack of benefit from fluticasone propionate was most likely due to failure of the drug to penetrate the viscid mucus lining the airways. It is suggested a large multicentre trial with higher doses given for a longer time by a different delivery system is required to assess efficacy.